The Effect of Program Integrated with Self-efficacy and Empowerment on Self health Care Behaviors and Blood Sugar Level in Pregnant Women with Gestational Diabetes Mellitus - Lertsakornsiri, Maleewan; Watcharasindhu, Ponglada (Journal of health and health management, 2023)
This research was a quasi-experiment with pretest-posttest two groups design. The purpose of this research was to study the effect of program integrated with self-efficacy and empowerment on self health care behaviors and blood sugar level in pregnant women with gestational diabetes mellitus. The samples were selected by purposive sampling composed of the 60 pregnant women with gestational diabetes mellitus at antenatal clinic in the Rajvithi Hospital, that separated into two groups (experimental group and control group). The research tool was a test of knowledge in gestational diabetes mellitus, and questionnaire including personal data, self-efficacy, and self health care behaviors. The research tool was validated by 3 experts. The content validity index (CVI) was .80, the reliability were .79, .78, and .89, respectively. The data were analyzed by frequency, percentage, mean, standard deviation, and t-test. The results indicated that after experiment the pregnant women with gestational diabetes mellitus type A1 who used the program integrated with self-efficacy and empowerment have knowledge, self- efficacy, self-esteem, and self health care behaviors which were statistically higher than the control group at p<.05, .001. For the third time of the experiment group, both the FBS and 1 hour post-meal blood glucose levels were lower than the control group with statistical significance at the .05 level. This program can help pregnant women with gestational diabetes mellitus type A1 have knowledge, understanding, and confidence in their ability to act while having diabetes have good health care behaviors. It can control blood sugar effectively.